2014
DOI: 10.7314/apjcp.2014.15.12.4929
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between Breast Cancer Patients Younger and Older than 40 Years: Mammographic Findings

Abstract: Objective: To compare the mammogarphic appearance between breast cancer patients aged <40 and ≥40 years. Methods: Needle localization and biopsy of suspicious mammographic lesions identified 1,959 breast carcinomas in a single institution from Jun 2012 to Apr 2013. According to the age, we divided patients into two groups: <40 and ≥40 years old, and analyzed mammographic appearance separately. Results: Young patients had 44.2% foci with calcification, but old patients only had 39.4% (P<0.001). In younger group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…It is similar to a previous study conducted by Zhao et al in which circumscribed and microlobulated masses on mammography were more common among younger cases, and estimated at 13.9% in the younger group. 35 Regarding margin, there is an additional point that the most common mass margin was indistinct which is consistent with some previous studies. 35 In our research, all the neoplastic masses were hypoechoic which is compatible with previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…It is similar to a previous study conducted by Zhao et al in which circumscribed and microlobulated masses on mammography were more common among younger cases, and estimated at 13.9% in the younger group. 35 Regarding margin, there is an additional point that the most common mass margin was indistinct which is consistent with some previous studies. 35 In our research, all the neoplastic masses were hypoechoic which is compatible with previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…On breast cancer screening for young women, we should be aware of the features of mammograms in young patients with breast cancer to maintain high sensitivity. Zhao et al, (2014) showed that the number of young patients with a mammographic focus who had microcalcifications was significantly more than that of old patients (44.2% vs. 39.4%, P = 0.001). Additionally, considering the high prevalence of dense breasts among young women, microcalcifications are important findings in young patients with breast cancer.…”
Section: Discussionmentioning
confidence: 95%
“…Because of the high frequency of high-density breasts in young women, studies have assessed the characteristic findings in young women, particularly those with a mass and focal asymmetric density (Osako et al, 2007;Zhao et al, 2014). Few studies have examined the characteristics of breast microcalcifications on screening mammography in young women.…”
Section: Features Of Microcalcifications On Screening Mammography In mentioning
confidence: 99%
“…Mammographic density and the age-specific incidence of breast cancer differ markedly between women in Asian and Western countries [ 10 - 13 ]. Therefore, there may be differences in the relationship between breast density and breast cancer risk in Asian women [ 9 ], including Korean women [ 14 , 15 ], compared to women in Western countries.…”
Section: Introductionmentioning
confidence: 99%